Comparative evaluation of Gracilaria algae 3% cream vs Clobetasol 0.05% cream in treatment of plaque type psoriasis: A randomized, split‐body, triple‐blinded clinical trial. Issue 6 (8th October 2020) - Shatalebi, Mohammad Ali; Bokaie Jazi, Safoura; Yegdaneh, Afsaneh; Iraji, Fariba; Siadat, Amir Hossein; Noorshargh, Pegah
Abstract: Gracilaria algae is red macro algae which has demonstrated considerable anti‐inflammatory effects. Our objective was to compare the efficacy of Gracilaria algae topical cream 3% vs Clobetasol cream 0.05% in treatment of plaque‐type psoriasis. Thirty adult patients with baseline modified Psoriasis Area and Severity Index (PASI) score ≤12 were randomized to receive either Clobetasol or Gracilaria algae cream on right or left‐sided symmetric plaques once daily for 8 weeks and follow‐up of 4 weeks. Modified PASI score, patient's satisfaction using VAS and global physician assessment score were assessed to evaluate clinical response. Thirty patients with 94 symmetrical psoriasis plaques were enrolled in this trial. The mean baseline modified PASI score of both sides was similar; however, at the end of trial, modified PASI score was reduced more on the sides treated with Gracilaria algae cream (0.80 ± 0.19% vs 0.63 ± 0.25%, P  < .05). No significant difference was found regarding mean physician global assessment score between the two groups ( P  > .05). Patients' satisfaction was significantly higher in favor of algae cream only at week 8 of the intervention ( P  < .05). Gracilaria algae cream can be an effective and safe alternative of Clobetasol in the treatment of plaque type psoriasis.